Status gizi, pengetahuan dan kecukupan konsumsi air pada siswa SMA Negeri 12 Kota Banda Aceh - Saiful Bakri (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2019)
Fluid requirements increased in adolescents is caused by increased physical activity so that the body needs water to complied of body fluids. Adequacy of fluids is related to the level of knowledge and nutritional status of adolescents. Knowledge affects the act of consuming water. This study aims to related nutritional status, knowledge to the adequacy of water consumption. This research was conducted at Senior Hight School 12 Banda Aceh city. This research is descriptive analytic with crossectional design. The total sample was 64 people with stratified random sampling and data collection methods using questionnaires. Results: normal of nutritional status (92,2%), knowledge level of drinking water consumption is quite good (54,7%), inadequate water consumption (70,3%). There is no relationship between nutritional status (p= 0,318), knowledge (p= 0,149) with adequate water consumption. Conclusion: nutritional status and knowledge are not related to the adequacy of water consumption. adolescents need information about water consumption needs so that dehydration does not occur during daily activities.Peningkatan kebutuhan cairan pada remaja disebabkan karena meningkatnya aktifitas fisik sehingga tubuh memerlukan air untuk memenuhi kebutuhan cairan tubuh. Kecukupan cairan berkaitan dengan tingkat pengetahuan dan status gizi remaja. Pengetahuan mempengaruhi tindakan mengkonsumsi air. Penelitian bertujuan untuk hubungan status gizi, pengetahuan dengan kecukupan konsumsi air. Penelitian ini di lakukan di SMAN 12 kota Banda Aceh. Penelitian ini bersifat deskriptif analitik dengan desain crossectional. Total sampel sebanyak 64 orang dengan metode pengambilan sampel stratified random sampling dan pengumpulan data di lakukan menggunakan kuasioner.Hasil :status gizi remaja normal (92.2%), tingkat pengetahuan konsumsi air minum cukup baik (54.7%), ketidakcukupan konsumsi air ( 70.3%). Tidak ada hubungan antara status gizi (p= 0,318), pengetahuan (p=0,149) dengan kecukupan konsumsi air. Kesimpulan: status gizi dan pengetahuan tidak berhubungan dengan kecukupan konsumsi air. Remaja membutuhkan informasi tentang kebutuhan konsumsi air agar tidak terjadi dehidrasi saat melakukan aktifitas.